DAMPAK PSIKOLOGIS PENDIDIKAN DARING DAN POTENSI STRATEGI MITIGASI SELAMA KRISIS COVID-19 PADA SISWA SEKOLAH DASAR - Widiastuty, Arum; Ruslanjari, Dina; Mei, Estuning Tyas Wulan; Puspitasari, Diana (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
The COVID-19 pandemic has had an effect on education, causing school closures and online learning, one of which being at an elementary school in Sriharjo Village. The disadvantages of online learning in Sriharjo elementary schools include a lack of supported learning facilities, a restricted choice of learning materials and media used, and limited internet access. The purpose of this study is to investigate the effect of online learning on the psychological well-being of primary school students, as well as the possibility for mitigation strategies during the COVID-19 crisis. This is qualitative research using a case study approach. The findings reveal that online learning has a positive psychosocial impact because it develops a sense of competition and encourages students to be more creative while dealing with difficulties or assignments. Students may experience negative psychosocial effects such as decreased work productivity, difficulty solving problems, decreased interaction skills and learning achievement, reduced ability to participate in groups, disrupted relationships with friends and peers, child withdrawal, sleep disturbances, unreasonable fear, lucidity and nightmares, and difficulty concentrating. The positive effects on mental health include being aware of one's own abilities and interests, being able to respond appropriately to problems, finding positive and productive activities to participate in, eating regularly, and feeling comfortable in social situations. The negative effects on students' mental health include feeling sad and disappointed due to limited activities, feeling down over decrease learning achievement, feeling homesick for friends and teachers, feeling bored while studying at home, and in certain cases, stressful conditions. This article suggests creating a curriculum that can adapt to a variety of issues during COVID-19 and changes in the post-pandemic learning environment. It also discusses the possibility of developing curriculum for post-COVID-19 schools.